IMPLEMENTATION OF SEXUAL EDUCATION PROGRAMS FOR ADOLESCENTS IN INDONESIA: NARRATIVE REVIEW - Dewi Susanti; Alsri Windra Doni (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2021)
Premarital sexual behavior adolescents in Indonesian continues to increase from year to year. If not addressed will have an impact on various aspects of physical, psychosocial and economic. This effect is seen in the incidence of unwanted pregnancy, abortion, dropping out of school and being infected with an STI. Various studies have shown that one of the efforts to overcome it by increasing adolescent knowledge about reproductive health. This study aims to examine the implementation of sexual education programs in adolescents to find the best methods that can be integrated into the Indonesian government program.The research method is literature review by analyzing 16 selected literature obtained from Google Scholar, J.Stor.org, Springerlink and Proquest. Criteria for articles chosen is relevant to the title, taken from 2014-2020.The literature review results found that the cause of the unsuccessful sexual education program for adolescents in Indonesia is related to the factors of cost, human resources, commitment, organizational structure and administration. Also in Indonesia sexual education is still part of the extra-curricular although WHO has recommended a comprehensive sexual education program (CSE) by involving all related components namely parents, schools, communities, government and adolescents themselves and integrated in the core curriculum. The CSE program needs to be strengthened by integrating cultural and religious norms and values, friendly education methods and other aspects.The recommendation of this research is to provide a sexual education curriculum and be included in the core curriculum of the school. In addition, it is necessary to create a framework for sexual education in adolescents starting from the family, school, community level and policy makers. For the success of the program so that the material and methods of sexual education are adjusted to the characteristics of adolescents, cultural factors, religion, norms and values ​​in the community.